2022
DOI: 10.1101/2022.11.07.515451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antifungal activity of selected lactic acid bacteria from olive drupes

Abstract: In this study, 16 Lactobacilli (LABs) isolated from the drupes of olive (Olea europaea) oil varieties were identified asLactiplantibacillus plantarum(seven isolates),Pediococcus pentosaceus(six isolates),Enterococcus faecium(two isolates) andStreptococcus salivarius(a single isolate) by peptide mass fingerprinting and sequencing of the 16S rRNA. Antifungal activity of LABs and their cell-free fermentates (CFSs) against several plant pathogenic fungi and oomycetes (fungi sensu lato), includingAlternaria,Aspergi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Panebianco and Caridi [ 41 ] also reported that 91% of the isolated LAB strains exhibited antagonistic activity against P. crustosum and 18% against Aspergillus sp., with the most representative strains being identified as L. pentosus and Fructilactobacillus sanfranciscensis . Simões et al [ 14 ] and Riolo et al [ 43 ] identified several LAB, isolated from olives, that showed strong inhibiting properties against P. nordicum . The potential of LAB as biopreservative agents in black olives was also studied in the work of El Oirdi et al [ 44 ], in which CFS from L. plantarum showed an important bioprotective effect against attack by A. fumigatus , delaying fungus growth for about 30 days, pointing to the possible use of indigenous isolates of lactic acid bacteria in the prevention of foods, such as fermented table olives.…”
Section: Discussionmentioning
confidence: 99%
“…Panebianco and Caridi [ 41 ] also reported that 91% of the isolated LAB strains exhibited antagonistic activity against P. crustosum and 18% against Aspergillus sp., with the most representative strains being identified as L. pentosus and Fructilactobacillus sanfranciscensis . Simões et al [ 14 ] and Riolo et al [ 43 ] identified several LAB, isolated from olives, that showed strong inhibiting properties against P. nordicum . The potential of LAB as biopreservative agents in black olives was also studied in the work of El Oirdi et al [ 44 ], in which CFS from L. plantarum showed an important bioprotective effect against attack by A. fumigatus , delaying fungus growth for about 30 days, pointing to the possible use of indigenous isolates of lactic acid bacteria in the prevention of foods, such as fermented table olives.…”
Section: Discussionmentioning
confidence: 99%